Novel insights from meta-analysis: the efficacy of ginsenosides in non-alcoholic fatty liver disease - Hao, Liyuan; Peng, Qing; Li, Shenghao; Hu, Xiaoyu; Yan, Huimin (Frontiers in Pharmacology, 2025)
BackgroundThe global prevalence of non-alcoholic fatty liver disease (NAFLD) has surged, largely driven by modern lifestyle changes and dietary shifts. As these factors profoundly impact human health, exploring effective therapeutic strategies for NAFLD has become a pressing medical concern. Previous studies have suggested that ginsenosides may offer a potential treatment approach for NAFLD by reducing oxidative stress and controlling inflammation. However, its efficacy and safety remain unclear. Therefore, the aim of this systematic review and meta-analysis is to evaluate the role of ginsenosides in the treatment of NAFLD.MethodsWe searched for relevant studies published through September 2024, including databases such as PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang Data. The SYstematic Review Center for Laboratory animal Experimentation (SYRCLE) Animal Experiment Bias Risk Assessment Tool was used to evaluate the quality of the literature. Subsequently, Review Manager (RevMan, version 5.3) and STATA 15 software was utilized for data analysis.ResultsFinally, 30 studies involving a total of 604 animals were included in the analysis. The results showed that, compared with the model group, ginsenosides significantly reduces total cholesterol (TC), triglycerides (TG), alanine aminotransferase (ALT), aspartate aminotransferase (AST), low-density lipoprotein cholesterol (LDL), body weight, liver weight, liver index, serum insulin, tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1), interleukin-6 (IL-6) and NAFLD Activity Score (NAS). Due to the high heterogeneity, we conducted subgroup analyses of the main results ALT, AST, TC and TG by animal strains, modeling methods, administration methods, ginsenoside dosages and types of ginsenosides. The results showed that the heterogeneity of TC may be derived from differences in modeling methods. The results showed that the heterogeneity of TC may be derived from differences in modeling methods.ConclusionIn this study, we summarized the molecular mechanism of ginsenosides in regulating NAFLD, mainly focusing on inhibiting inflammation and oxidative stress, improving insulin sensitivity, and regulating intestinal flora. Preclinical evidence indicates that ginsenosides represent a novel therapeutic avenue for NAFLD. The mechanism of ginsenosides in treating NAFLD may involve anti-inflammation, antioxidation, improving insulin resistance, and regulating intestinal flora. However, the inclusion of studies with low methodological quality and the existence of publication bias may undermine the validity of the results. To fully elucidate the mechanisms underlying the therapeutic effects of ginsenosides, future research should employ more rigorous experimental designs and conduct comprehensive investigations.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/.